Manajemen Kurikulum: Orientasi Manajemen Kurikulum Pendidikan Islam dalam Perspektif Al-Qur'an - azmi, arida ulul (Maliki Interdisciplinary Journal, 2024)
A good curriculum is a curriculum that is in accordance with what is experienced and felt by students. Curriculum Management itself is a management system that is collaborative, comprehensive and systematic to achieve curriculum goals. The autonomy given to institutions and schools allows them to manage the curriculum independently, while prioritizing the needs and vision and mission of the institution, without overriding the established national policies. The Islamic Education Curriculum itself is found in many modern and Salafiyah (traditional) Islamic boarding schools. The characteristics of the Islamic education curriculum prioritize religious and moral values as the main goal, the balance between science and art, and a broad and comprehensive coverage. The Islamic education curriculum in the perspective of the Qur'an is found in Surah At-Taubah verse 122 which from a Qur'anic perspective, management is considered very crucial. One aspect is planning, which is a step taken to achieve certain results in a specified time and space.